(untitled) (Tamaddun, 2025)
The poetry anthology Dibalik Jas Putih by medical students has a medical lexicon and interconnected language styles. This study aims to inventory the medical lexicon in the poetry anthology, analyze the patterns and functions of the dominant language style, and reveal the correlation between the authors’ educational backgrounds and the stylistic characteristics of the works. This study uses a descriptive qualitative method with an integrated stylistic approach. The data is sourced from the poetry anthology Dibalik Jas Putih by medical students. Data collection used the read-and-record technique. The data was then analyzed in three stages: 1) identification of medical lexicon (linguistic corpus), 2) classification of language style (Leech & Short), and 3) interpretation of meaning based on the context of creation (critical discourse analysis). The first research results found 10 medical lexicons in 6 poems from the poetry anthology Dibalik Jas Putih along with the frequency of occurrence and lexical meaning from Dorland’s Medical Dictionary. There were symbolic figures of speech, metaphors, and similes found from the ten medical lexicons through Leech & Short’s stylistic theory. The final research results obtained the contextual meaning of each medical lexicon along with its stylistic function.